On Olive Oil and Perfume Production in Iron Age IIA Tell es Safi/Gath, Israel - Eitam, David (Palestine exploration quarterly, 2022)
The statement by Maeir and colleagues ‘that production of olive oil was a central aspect in the agricultural production in [Tell es-Safi/Gath] region already during the Iron I and Iron IIA’ (Maeir et al. 2020, 129) is being challenged here. The authors’ conclusions are examined by analysing the Iron Age IIA devices of Tell es-Safi/Gath, facing the development of olive oil production in Iron Age Israel. Perfume is the proposed alternative product manufactured by the installations of Tell es-Safi/Gath.